8 - Transformative Autonomy: Mixed Notes from Teachers to Higher Education - Nel, Willy (Journal of Higher Education in Africa, 2022)
Transformative autonomy is ‘the form of autonomy in which school role players, such as teachers, have the urge to be involved with fellow role players in education development initiatives towards social transformation which contributes to democracy’ (Nel 2014: 790). This theoretical construct was formulated to narrow the gap between teaching practice and societal concerns since it recognizes that teachers do have a certain degree of au- tonomy over their professional practice but also a responsibility towards the evolving South African democracy. In an effort to test the veracity of transformative autonomy as a theoretical construct data was gathered from three sets of participants: twenty-six postgraduate students, thirteen rural primary school teachers and thirty-one conference delegates. Some key findings are that participants generally acknowledged their control over curriculum aspects and some degree of control over matters of discipline. A curious finding is the appearance of discipline as an aspect over which some participants felt they have control and other participants felt they had no control. These findings, and others, are discussed in the context of transformative autonomy. One of the main conclusions is that these par- ticipants display an intuitive understanding of their autonomy as teachers but that they still do not have a clear idea of how to link their expertise to societal transformation. It is lastly concluded that the issue of autonomy has epistemological implications insofar as the condition of knowledge production, reproduction and dissemination is concerned, all of which impact on teachers’ intellectual integrity. Higher education, therefore, is alerted to its responsibility in teacher training.